Chemical composition of wonderful kola (Bucchlozia coriacea) and breadfruit (Artocarpus altilis) seeds grown in south–south, Nigeria - Aremu, MO; Passali, DB; Ibrahim, H; Akinyeye, RO (Bangladesh Journal of Scientific and Industrial Research, 2018)
The proximate and amino acid compositions of Artocarpus altilis and Bucchholzia coriacea were investigated using standard analytical techniques. The respective proximate composition (%) for the Artocarpus altilis and Bucchholzia coriacea samples were: Moisture (5.91 and 5.67); ash (4.39 and 5.13); crude fat (4.42 and 2.76); crude protein (12.27 and 14.78); crude fibre (7.10 and 6.27); carbohydrate (65.91 and 65.39). The calculated fatty acids and metabolizable energy for the Artocarpus altilis and Bucchholzia coriacea samples were 3.54 and 2.21 %; 1492.60 and 1465.01 kJ/100 g, respectively. The most abundant minerals in Artocarpus altilis and Bucchholzia were potassium (658.42 and 369.64 mg/100 g) and phosphorus (382.55 and 261.38 mg/100 g), respectively. The amino acid profile revealed that Artocarpus altilis and Bucchholzia coriacea samples contained nutritionally useful quantities of most of the essential amino acids. The total essential amino acids (TEAA) (with His) were 31.14 and 34.40 g/100 g crude protein for the Artocarpus altilis and Bucchholzia coriacea samples, respectively. The first limiting amino acid was Met + Cys (TSAA) for all the samples and calculated isoeletric points (ρl) were 3.52 and 4.05 for Artocarpus altilis and Bucchholzia coriacea, respectively. Bangladesh J. Sci. Ind. Res.53(2), 125-132, 2018